Antiplasmodial, antioxidant and immunomodulatory activities of ethanol extract of Vernonia amygdalina del. Leaf in Swiss mice - Ehimwenma Omoregie; Anirban Pal (Mashhad University of Medical Sciences, 2016)
Objective: Vernonia amygdalina (V.  amygdalina) leaf is locally employed in the Southern region of Nigeria in the treatment of malari a infection. This study evaluated the in vivo antiplasmodial, antioxidant and immunomodulatory effect of ethanol extract of V.  amygdalina leaf. Materials and Methods: The active principles of the dried leaf were extracted with ethanol. For quality validation, chemical finger-print of the extract was performed through high performance thin layer chromatography (HPTLC). The extract was assessed for antiplasmodial activity by the standard four-day suppressive test on Plasmodium berghei (ANKA) infected male Swiss mice (six weeks old) placed into five groups of six animals each. Result: The absorption spectra from the HPTLC revealed several peaks suggesting presence of some bioactive compounds. Results from the in vivo study showed that the ethanol extract of the plant leaf was significantly active against P. berghei in a dose-dependent manner with the minimum and maximum activity observed in the mice treated orally with 100mg/kg (% inhibition of 23.7%) and 1000 mg/kg (% inhibition of 82.3 %) of the extract, respectively, on day four of the study. There was also a dose-dependent decrease (p